A COMPARATIVE ANALYSIS OF COMPLIMENTS IN CELEBRITIES’ INSTAGRAM AND TIKTOK COMMENTS - Fajri, Aulia Nur; Sudarwati, Emy (Universitas Islam Sumatera Utara (UISU), 2024)
The purpose of this research is to examine the complementing strategies employed in celebrity Instagram and TikTok comments, as well as the differences between these strategies. This research used qualitative methods. The researchers selected 150 comments on Instagram and 150 comments on TikTok. Then, the researchers analyzed it using Ye's theory to analyze the compliments strategy and used Manes Wolfson's theory to analyze the syntactic pattern. Furthermore, the researchers compared the use of compliments on Instagram and Tiktok. The findings from this research showed that direct compliments tend to be used on both Instagram and TikTok. The study also discovered seven different types of direct compliments, including NP is/looks (really) ADJ; I (really) like/love NP; PRO is (really) (a) ADJ NP; You V (really) (a) ADJ NP; You V (NP) (really) ADV; You have (a) (really) ADJ NP; and ADJ NP! the use of form ADJ NP! is more likely to be used on Instagram. Meanwhile, the form NP is/looks (really) ADJ is more likely to be used on TikTok.